Simultaneous removal of ammonium and nitrate by HDTMA-modified zeolite - Tao, Quan (Water science and technology : a journal of the International Association on Water Pollution Research, 2015)
In this study, surfactant (hexadecyltrimethylammonium, HDTMA) modified zeolite (clinoptilolite) (SMZ) was used for simultaneous removal of ammonium and nitrate in wastewater, and the sorption properties of SMZ were determined. Results showed that natural clinoptilolite had good affinity for ammonium, but low sorption ability for nitrate, and the ammonium sorption process was well described by the pseudo-second order kinetic model. The SMZ had a significant enhancement on nitrate sorption and could simultaneously remove ammonium and nitrate at specific conditions, with removal efficiency up to 93.6% and 81.8%, respectively. The sorption process fitted well with the Langmuir isotherm. Orthogonal experiments showed that ammonium concentration was the most important factor for ammonium sorption on SMZ. However, surfactant loading was the major factor for nitrate sorption. Meanwhile, phosphate did not interfere with nitrate removal. Semi-empirical quantum mechanics molecular simulation indicated that electrostatic attraction existed between HDTMA and nitrate. Results of this study demonstrated that SMZs may have great potential for removing cations and anions simultaneously in the aquatic environment